Wprowadzenie rachunku kosztów działań w przedsiębiorstwie komunikacji samochodowej - Konstantyn, Krzysztof (Conception of Introduction of Activity Based Costing in Enterprise of Car Transport, 2007)
The attention in the article is directed to the search in the range of new solutions of limiting the quantity of indirect costs. It seems that the initiating the activity based costing in an enterprise of car transport can be with such a solution.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 274-282